Analysis and enhancement of the new Eurocode 5 formulations for the lateral elastic deformation of LTF and CLT walls. (January 2023) - Aloisio, Angelo; Boggian, Francesco; Sævareid, Håkon Østraat; Bjørkedal, Johan; Tomasi, Roberto
Abstract: This paper analyses the analytical formulations for the lateral elastic deformation of Light Timber Framed (LTF) and Cross-Laminated Timber (CLT) shear walls according to the new Eurocode 5 (EC5) proposal. Finite Element (FE) models and the Standard predictions are compared by emphasizing the role of each deformation contribution. A total of 1830 comparisons between analytical and numerical estimations are carried out by exploiting the Application Programming Interface of SAP2000 to modify the FE model parameters automatically. The parametric analyses proved that the numerical and analytical predictions are pretty consistent. Furthermore, in both LTF and CLT shear walls, the estimates for in-plane shear and rigid body sliding are in excellent agreement. Conversely, the analytical formulas for kinematic rocking are generally conservative for LTF and monolithic CLT shear walls, with an approximate 18%–19% discrepancy. The analytical expressions of the upcoming EC5 perfectly match the numerical model for segmented CLT shear walls under lateral forces and no vertical load. However, the presence of the vertical load determines a significant bias. Additionally, the predictions for bending deformations are not in good agreement. Therefore, the paper discusses possible enhancements for the equations proposed in the next generation of Eurocodes for the rocking deformation of segmented CLT walls to better conform with FE predictions.